2010
DOI: 10.1136/gut.2009.196519
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoural immunity by virus-mediated immunogenic apoptosis inhibits metastatic growth of hepatocellular carcinoma

Abstract: Proteasome inhibition during virotherapy disrupts the UPR, leading to enhanced ER stress-induced apoptosis, improved local oncolysis and antitumoural immunity. The results suggest that combining intratumoural virotherapy with adjuvant systemic therapies, which specifically support the function of the virotherapy as an antitumoural vaccine, is a promising immunotherapeutic strategy against HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…Results of all these endeavours are eagerly awaited as well as the final incorporation of immune cancer control as a potential therapeutic option. 133134 …”
Section: Treatment: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Results of all these endeavours are eagerly awaited as well as the final incorporation of immune cancer control as a potential therapeutic option. 133134 …”
Section: Treatment: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Unfortunately, its therapeutic efficacy appears disappointing in clinical trials, and a standard therapeutic method has not been established. Recently, attention has focused on a variety of vaccines investigated in experimental studies comprising patients with HCC, because they have been reported to greatly induce a tumorspecific immune response against tumor cells (4,5). As a result, identifying and establishing a novel approach for the prevention of HCC development and recurrence (i.e.…”
mentioning
confidence: 99%
“…Although the exact mechanisms of these immunotherapies are not fully clear, it has been reported that CTLA-4 inhibition led to expansion of CD8 T cells directed against mutated tumor epitopes (46,47). CD8 T-cell responses are also important mediators of antitumor cytotoxicity following virotherapy whereby effective oncolytic inflammation in the tumor tissue is an important precondition to fully exploit these promising functions (10,48,49). The sum of proteinencoded mutations of a single tumor, the mutanome, provides an attractive pool of neoantigenic targets that can be rationally predicted by tumor exome sequencing and algorithm-based search (46,50).…”
Section: Discussionmentioning
confidence: 99%